In vitro incorporation of a cell‐binding protein to a lentiviral vector using an engineered split intein enables targeted delivery of genetic cargo. Issue 12 (12th August 2015) - Chamoun‐Emanuelli, Ana M.; Wright, Gus; Roger, Smith; Münch, Robert C.; Buchholz, Christian J.; Chen, Zhilei
ABSTRACT: Gene therapy represents a promising therapeutic paradigm for addressing many disorders, but the absence of a vector that can be robustly and reproducibly functionalized with cell‐homing functionality to mediate the delivery of genetic cargo specifically to target cells following systemic administration has stood as a major impediment. In this study, a high‐affinity protein–protein pair comprising a splicing‐deficient naturally split intein was used as molecular Velcro to append a HER2/neu‐binding protein (DARPin) onto the surface of a binding‐deficient, fusion‐competent lentivirus. HER2/neu‐specific lentiviruses created using this in vitro pseudotyping approach were able to deliver their genetic reporter cargo specifically to cells that express the target receptor at high levels in a co‐culture. We envision that the described technology could provide a powerful, broadly applicable platform for the incorporation of cell‐targeting functionality onto viral vectors. Biotechnol. Bioeng. 2015;112: 2611–2617. © 2015 Wiley Periodicals, Inc. Abstract : A novel strategy for reprogramming the cell‐type specificity of lentiviral vectors via robust and reproducible in vitro attachment of a target‐cell‐binding protein to the lentivirus surface is described. A high‐affinity protein–protein pair comprising a splicing‐deficient naturally split intein is used to load a binding‐deficient, fusion‐competent lentivirus with a target‐cell‐binding molecule ("binder"). This approach could provide a powerful, broadly applicable platform for altering the cell‐type specificity of viral vectors for gene therapy applications.